Pengaruh Budaya Organisasi, Struktur Komunikasi dan Sistem Penghargaan Terhadap Kinerja Pegawai Pada Kantor Badan Kepegawaian Pengembangan SDM Kota Batam - Lestari, Ernita; Muhidin, Deden; Manalu, Nelly Chandrawati; Herman, Hendri (eScience Humanity Journal, 2024)
This study was conducted with the aim to determine the effect of organizational culture, communication structure and reward system on employee performance at the Batam City HR Development Staffing Agency office. The population in this study were employees of the Batam City HR Development Staffing Agency. The total population is 52 employees. The determination of the number of samples using saturated sample technique, so that the number of samples was 52 employees. The sampling technique is probability sampling. Data collection was carried out by distributing questionnaires to respondents. The data that has been collected is processed using SPSS data processing software. From the results of the study, it is known that organizational culture has a significant effect on employee performance, communication structure has a significant effect on employee performance, the reward system has no significant effect on employee performance. Simultaneously, it is known that organizational culture, communication structure and reward system have a significant effect on employee performance. The adjusted R square value is 0.584 or 58.4%. This means that organizational culture, communication structure and reward system are able to explain employee performance by 58.4%, while the remaining 41.6% is influenced by other factors not included in this research model.